2020
DOI: 10.1097/won.0000000000000626
|View full text |Cite
|
Sign up to set email alerts
|

Bedside Technologies to Enhance the Early Detection of Pressure Injuries

Abstract: Each year, more than 2.5 million people in the United States develop pressure ulcers. These skin lesions bring pain, associated risk for serious infection, and increased health care utilization. Moreover, the Centers for Medicare & Medicaid (CMS) no longer provides additional reimbursement to hospitals to care for a patient who has acquired a pressure ulcer while under the hospital's care. Thus, pressure ulcer prevention presents an important challenge in acute care hospitals. A number of best practices have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 24 publications
1
50
0
5
Order By: Relevance
“…15,17,18,[26][27][28][29][30][31] The role of localised inflammatory oedema/SEM was recognised as 'one of the earliest signs of cell death in pressure injuries' in the 2019 Clinical Practice Guidelines 24 emphasising the importance of SEM as an aetiological biomarker in predicting impending skin damage. 32 Results from this study add to the body of evidence that spatial SEM tests have clinical utility in aiding HCP determination of healthy versus damaged tissue. These spatial SEM results demonstrated key identifying features of fluctuations in absolute SEM values in healthy and pressure-damaged skin and tissue.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…15,17,18,[26][27][28][29][30][31] The role of localised inflammatory oedema/SEM was recognised as 'one of the earliest signs of cell death in pressure injuries' in the 2019 Clinical Practice Guidelines 24 emphasising the importance of SEM as an aetiological biomarker in predicting impending skin damage. 32 Results from this study add to the body of evidence that spatial SEM tests have clinical utility in aiding HCP determination of healthy versus damaged tissue. These spatial SEM results demonstrated key identifying features of fluctuations in absolute SEM values in healthy and pressure-damaged skin and tissue.…”
Section: Discussionmentioning
confidence: 66%
“…In the aggregate, results from this study in combination with laboratory studies, 14 inter-operator reliability studies, 19 damaged and healthy tissue studies, 26,49 longitudinal assessments 18 and other SEM studies 15,29,31,32,35,[50][51][52] through different tests of SEM have repeatedly shown that SEM is a predictor and a reliable indicator of the early onset of pressure-induced skin and tissue damage. Furthermore, a health economics analysis performed by Padula et al (2020), shows that prevention using the SEM test is cost-saving and is dominant in quality interventions when compared to the current standard of PI/PU care.…”
Section: Discussionmentioning
confidence: 66%
“…Impedance devices (e.g. Nova ® Dermal Phase Meter, MoistureMeter D ® ) have examined device-dependent absolute SEM measures as an indicator of pressure-induced damage [37]. These devices have not been approved for patient use and are available for research only.…”
Section: Overview Of the Marketmentioning
confidence: 99%
“…In conclusion, evidence identified in a clinical systematic review supported the use of SEM measurement devices as effective tools for early pressure injury detection. 22 In this health economic analysis, SEM scanners are a cost-effective means of documenting pressure injury risk based on moisture levels on patients' skin and underlying soft tissue. This technology circumvents the high cost of most pressure injuries in facilities and may achieve an ROI in less than one year.…”
Section: Discussionmentioning
confidence: 99%